Kebutuhan Informasi Pemustaka dalam Teori dan Praktek - Fatmawati, Endang (Universitas Sanata Dharma Yogyakarta, 2015)
Information is vital to every user. The information needs of the user is very important of library service. Each user’s information needs are very diverse. Factors affecting information needs is very much. One of them depending on user characteristics and conditions in his environment. User information need is a factual situation of user in which occurs of gaps between the existing knowledge with the knowledge needed.Keywords: information needs, user needs, sources of information.